Manufacturing Non Adhesive Biobriquettes With Main Ingredients From Cow Manure Waste at Dairy Cows Teaching Factory - Rachmanita, Risse Entikaria; Aminullah, Muhammad; Susmiati, Yuana; Febriani, Siti Diah Ayu; Rudiyanto, Bayu (P3M Politeknik Negeri Jember, 2024)
Biobriquettes are solid energy source that comes from biomass that is compressed under a certain pressure. The development of non-adhesive biobriquettes has not been widely carried out. Teaching factory (TEFA) Dairy Cows Politeknik Negeri Jember have 51 cows and products ± 18-20 kg/day of cow manure which have not managed optimally. On the other side of district Jember produces 1,945 tons of coconut shell waste per year which is pill up, thrown away and used as stove fiel or simply burned. This research was conducted with an experimental method using composition variations of raws material and mixed material to obtain the best mixture ratio for biobriquettes, 4KS6AR (40% : 60%), 5KS5AR (50% : 50%), 6KS4AR (60% : 40%). The raw material for cow dung is cleaned from grass fibers. The coconut shells raw material that has been dried in the sun, then pyrolyzed at a temperature of approximately 200-250ºC for 6-7 hours, then ground to size of 40, 60 and 100 mesh. From the tests that have been carried out, the most optimal value to quality standards of National Standard of Indonesia (SNI) 01-6235-2000 is with a water content of 2,382 %, calorific value of 6.650 cal/g.